The architecture of fuzzy agent in rescuer monitoring system - Ahmad, A.H. (Science Publications, 2015)
Malaysia is a developing country and currently experiences a new emerging safety issue, which considered as critical. Country likes Malaysia is in aggressive mission to develop its country by year 2020. In the effort to achieve developed country, it requires development in each industry. There will be more works should be done by workers in the same duration compares to the last few years. With lots of tasks, people get stress out and this will lead to mistakes. Unsafe action sometimes cause accidents, worst may cause death. Especially hazardous works such as professional that need to work in manhole, low oxygen level confined space, underwater and fire fighter. This people need to be monitored during their operation to ensure their safety, thus the operation can complete successfully. In this study, we focus on the personal monitoring for fire fighter during their rescue operation. An agent based monitoring system using type-1 fuzzy logic is simulated to see the effect on personalâs parameters, such as breathing rate, breathing air level and body motion. A case study has been done to get the real fuzzy data which gathered by sensors to be tested using Mamdani type-1 fuzzy method. The result produced a reliable crisp output which then processed by the system to alerts the fire fighter any predicted accident that might happen. Intelligent agent adopted in this engine helps monitoring system act autonomously and process a reliable decision. This engine generate precise and reliable output from fuzzy input as we deal with human lives. As the result, injuries or fatality during works can be reduced. Â© 2015 Azwin Hazrina Ahmad, Ahmad Kamil Mahmood and Jafreezal Jaafar.